Spectroscopic and Dyeing Characteristics of the Yellow Dye from Morinda lucida (Brimstone Tree): Short Communication (Biological Sciences - PJSIR, 2005)
The yellow dye obtained from Morinda lucida plant, yield 16.5%, melting point 108-110 °C, showed absorption in the visible range 400-450 nm. Four major functional groups were identified at lmax of 435 nm. The IR and 1H-NMR spectra exhibited absorptions consistent with a conjugated polyfunctional structure. The yellow morinda dye is tentatively proposed as 4-benzoyl-2-amino acetaldehyde. The pigment imparted its brilliant yellow hue on the dyed cellulosic yarn and fabric with moderate fastness ratings to washing, perspiration, hot-pressing, however, having poor stability to high energy radiation.